Granbury's Texas Brigade : Diehard Western Confederates - Lundberg, John R. (Book collections on Project MUSE., 2012)
John R. Lundberg's compelling new military history chronicles the evolution of Granbury's Texas Brigade, perhaps the most distinguished combat unit in the Confederate Army of Tennessee. Named for its commanding officer, Brigadier General Hiram B. Granbury, the brigade fought tenaciously in the western theater even after Confederate defeat seemed certain. Granbury's Texas Brigade explores the motivations behind the unit's decision to continue to fight, even as it faced demoralizing defeats and Confederate collapse. Using a vast array of letters, diaries, and regimental documents, Lundberg offer.